Faktor-Faktor yang Berhubungan dengan Kejadian Diare Pada Balita - Meliyanti, Fera (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2016)
Diarrhea still often cause a remarkable event with the number of patients that a lot in a short time. In OKU District, diarrhea is still the fifth largest disease, one of which is Saung Naga Village to the number of visits diarrhea in infants in 2013 there were 159 (18.8%). This study aims to determine the factors associated with the incidence of diarrhea in infants. The research method using cross sectional approach. The population is all mothers with infants residing in Saung Naga Village as much as 843 mothers with a sample of 159 mothers. Sampling techniques with simple random sampling. The research location in Saung Naga Village UPTD Puskesmas Tanjung Baturaja Barat conducted in February to April 2014. Data were analyzed using Chi Square. The survey results revealed no correlation between health information with the incidence of diarrhea (p-value 0.001). There is a way of feeding correlation with the incidence of diarrhea (p-value 0.001). There is a correlation between the availability of latrines (p-value 0.001). There is a correlation between the provision of clean water to the incidence of diarrhea (p-value 0.001).Keywords: diarrhea, toddlers, health information.